Cloud computing at higher education institution!? - Banek Zorica, Mihaela (2011)
Cloud computing as a dynamical response to changing digital environment is generally defined as a third party service available for use when needed presents a departure from traditional static IT systems. It is no longer just a hype but more of a reality spreading from original commercial sector towards all aspects of our digital life. Educational environment with its e-learning is one of the segments rapidly becoming more involved in discussing and utilizing the potential of cloud services. On the Faculty of Humanities and Social Sciences, University of Zagreb we have always been oriented towards open source technologies therefore usage of emerging cloud computing services was tested and implemented for collaboration research activities at the Department of Information Sciences in a quite early stage of technology emergence. The question of the sustainability of cloud services usage on whole institution has arisen. Authors will present findings of research of students’ information behaviour and usage of web services in their private and educational life as well as position of teaching staff towards new technology. Through analysis of the body of literature authors will define positive and negative aspects and propose guidelines for implementation and utilization of cloud services in educational environment.